NILAI-NILAI PENDIDIKAN JIWA ISLAMI DALAM NOVEL BIDADARI BERMATA BENING KARYA HABIBURRAHMAN ELSHIRAZY - Ketry Okania (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2013)
This research is motivated by the uniqueeness found when reading the novel Bidadari Bermata Bening, including this novel that creates a story to build faith in the soul, and this novel is very strong with the motivation of the younger generation to achietive success. The purpose of this research is to describe: 1) The contents of parts of Islamic mental education in the novel Bidadari Bermata Bening by Habiburrahman El Shirazy; 2) The method of disclosing Islamic mental education messages in the novel Bidadari Bermata Bening by Habiburrahman ElShirazy; and 3) Islamic mental education values in the novel Bidadari Bermata Bening by Habiburrahman El Shirazy. This study uses a qualitative approach with a type of library research. The data source used in this research is the text in the novel Bidadari Bermata Bening, then the data collection tecnique used document analysis. The data analysis tecnique used is content analysis. Based on the analysis carried out, the results of this study are: (1) The contents of parts of Islamic mental education in Habiburrahman El Shirazy’s novel Bidadari Bermata Bening are upholding Islamic law, upholoding justice, teaching humality, rejecting religious beliefs, upholding Islamic teachings in marriage, trading according to Islamic teachings, rejecting capitalist arrogance, being careful in choosing friends, and being patient in upholding Islamic teachings; (2) The method of disclosing Islamic mental education messeges in the novel Bidadari Bermata Bening by Habiburrahman El Shirazy, which is conveyed through dialogue, prologue, monologue, character responses, and character descriptions; (3) The values of Islamic mental education in the novel Bidadari Bermata Bening by Habiburrahman El Shirazy, namely being obedient to worship, firm, not giving up anger, courage, patience, care, and keep promises.